The Medical Aspects of Safe Working (The Australasian Institute of Mining and Metallurgy, 1975)
In recent decades the awareness of environmental issues by the general public has developed at an accelerat- ing rate. This is the result of a number of factors including more scientific knowledge of environments and of the impacts of modern society upon them, higher levels of education, the opportunity for people to travel more, and the success of the various communication media in bringing in- formation to the communities of the world about such environmental crises or threats as the smogs of Los Angeles and London, the Torrey Canyon and Santa Barbara oilspills, Minamata disease in Japan, the spread of the Crown of Thorns starfish, the disposal of toxic industrial wastes into the Upper Rhine, the discovery of high mercury and zinc contents in marine foods in southern Australian waters, and the proposal to mine limestone at Precipitous Bluff in Tasmania.